Constitutional and Legal Support of Religious Freedom - ILYASSOV, Kairat; BOZHKARAULY, Altay; RUSTEMBEKOVA, Dinara (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018DO - 10.14505//jarle.v9.6(36).12, 2019)
The legal norm of freedom of conscience and religion is an inherent anthropic property of the right, realizing the freedom of a person in the choice of religious faith, unbelief, atheism, and scientific beliefs. The imperfection of the mechanism of legal regulation of religious freedom leads to violations and abuses of basic human rights. Overcoming the difficulties of the legislative process is possible when taking into account the factors of extra-legal influence on the established regime of freedom of conscience and religion in the state.